Effect of different origins on genes encoding key enzymes involved in the polysaccharide biosynthetic pathway in Hedysarum polybotrys Hand.-Mazz. - Zi Xia Wang; Hui Ni Yang; Yan Ping Wang; Yan Jun Jia; Yan Zhang; Li Dong; Fang Di Hu; Guo Lin Chai (PLoS ONE, 2025)
Radix Hedysari (HP) is a traditional Chinese medicine that has gained widespread attention for its tonic effects. Environmental factors significantly influence the active components in HP, notably Radix Hedysari polysaccharides (HPS), which are the principal active constituents. To date, no studies have reported on the environmental impact on the accumulation and biosynthesis of HPS. This research aims to evaluate the HPS accumulation and its biosynthetic pathways across different environments. We measured the HPS levels in samples from the core geographic area (geo-authentic product region) in Wudu, Gansu Province (WD), and a non-core geographic area (non-geo-authentic product region) in Tanchang, Gansu Province (TC), and conducted transcriptomic analyses. The HPS content in HP from WD (HP-WD, 12.14 ± 0.17 mg/g) was significantly higher than that in HP from TC (HP-TC, 5.48 ± 0.29 mg/g). Our investigation into the biosynthetic pathways of HPS showed that 21 enzymes, encoded by 198 unigenes, are involved. We identified 50 unigenes encoding 15 enzymes as differentially expressed genes (DEGs), indicating that approximately 71.4% of these enzymes are substantially affected by environmental factors. Heat map analysis of these 50 DEGs clearly differentiates HP-WD from HP-TC. Pearson correlation analysis revealed that the regulatory genes for 11 key enzymes have a significant positive correlation with HPS content (P <  0.05, r >  0.8). Consequently, the HP-WD is more likely to accumulate polysaccharides than HP-TC, potentially due to the activity of the aforementioned 11 key enzymes. This study provides theoretical support for the enhanced HPS content and quality assessment of HP sourced from the geo-authentic product region.